Bauran pemasaran, kualitas pelayanan terhadap keputusan pembelian berdampak pada loyalitas konsumen Apotek - Alfi Syahrin; Maura Linda Sitanggang; Indah Masri; Amelia Oktrivina (Jurnal STEI Ekonomi, 2023)
Changes in the pharmaceutical business paradigm, one of which is pharmacies, happened because of the Public Medical coverage program. Progressions might affect pharmacies, such as decreasing prescription acceptance, thereby potentially losing consumers. Data from Cipayung District, East Jakarta, for 2017-2022 shows 40 pharmacies, 28 pharmacies (70 percent) stayed standing, and 12 pharmacies (30 percent) closed. The research aims to determine the influence of the marketing mix and service quality on purchasing decisions and their impact on pharmacy consumer loyalty—Quantitative Research Methods. Sampling used a simple random sampling method; data was processed using Smart PLS. The sample determined using the Slovin formula was 100 respondents utilizing a survey. Research results show that marketing mix influences purchasing decisions. Service quality affects purchasing decisions. Marketing mix influences consumer loyalty. Service quality influences consumer loyalty. Purchasing decisions influence consumer loyalty. Marketing mix influences consumer loyalty through purchasing decisions. Service quality affects consumer loyalty through purchasing decisions. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.